Retrometabolic drug design and targeting - Bodor, Nicholas (Wiley, 2013)
BInnovative approach to drug design that's more likely to result in an approvable drug product/b/ Retrometabolic drug design incorporates two distinct drug design approaches to obtain soft drugs and chemical delivery systems, respectively. Combining fundamentals with practical step-by-step examples, iRetrometabolic Drug Design and Targeting/i gives readers the tools they need to take full advantage of retrometabolic approaches in order to develop safe and effective targeted drug therapies. The authors, both pioneers in the fields of soft drugs and retrometabolic drug design, offer valuable ideas, approaches, and solutions to a broad range of challenges in drug design, optimization, stability, side effects, and toxicity./ iRetrometabolic Drug Design and Targeting/i begins with an introductory chapter that explores new drugs and medical progress as well as the challenges of today's drug discovery. Next, it discusses:/ ulliBasic concepts of the mechanisms of drug action/liliDrug discovery and development processes/liliRetrometabolic drug design/liliSoft drugs/liliChemical delivery systems/li/ul Inside the book, readers will find examples from different pharmacological areas detailing the rationale for each drug design. These examples set forth the relevant pharmacokinetic and pharmacodynamic properties of the new therapeutic agents, comparing these properties to those of other compounds used for the same therapeutic purpose. In addition, the authors review dedicated computer programs that are available to support and streamline retrometabolic drug design efforts./ iRetrometabolic Drug Design and Targeting/i is recommended for all drug researchers interested in employing this newly tested and proven approach to developing safe and effective drugs.